Mast Cell Dependent Vascular Changes Associated with an Acute Response to Cold Immersion in Primary Contact Urticaria - Meyer, Joseph (Public Library of Science, 2013)
BACKGROUND: While a number of the consequences of mast cell degranulation within tissues have been documented including tissue-specific changes such as bronchospasm and the subsequent cellular infiltrate, there is little known about the immediate effects of mast cell degranulation on the associated vasculature, critical to understanding the evolution of mast cell dependent inflammation. OBJECTIVE: To characterize the microcirculatory events that follow mast cell degranulation. METHODOLOGY/PRINCIPAL FINDINGS: Perturbations in dermal blood flow, temperature and skin color were analyzed using laser-speckle contrast imaging, infrared and polarized-light colorimetry following cold-hand immersion (CHI) challenge in patients with cold-induced urticaria compared to the response in healthy controls. Evidence for mast cell degranulation was established by documentation of serum histamine levels and the localized release of tryptase in post-challenge urticarial biopsies. Laser-speckle contrast imaging quantified the attenuated response to cold challenge in patients on cetirizine. We found that the histamine-associated vascular response accompanying mast cell degranulation is rapid and extensive. At the tissue level, it is characterized by a uniform pattern of increased blood flow, thermal warming, vasodilation, and recruitment of collateral circulation. These vascular responses are modified by the administration of an antihistamine. CONCLUSIONS/SIGNIFICANCE: Monitoring the hemodynamic responses within tissues that are associated with mast cell degranulation provides additional insight into the evolution of the acute inflammatory response and offers a unique approach to assess the effectiveness of treatment intervention.